Analisa Termal Sistem Pemanas pada Alat Mesin Cetak Baut Platik Skala UMKM - Fitrah Ramadhan, Panji; Gunawan Hidayat (CV. Aksara Global Akademia, 2025)
This study aims to analyze the thermal performance of the heating system in a small-scale plastic bolt molding machine using LDPE material, in order to determine process parameters that are efficient while maintaining product quality. The method used includes experimental testing at two set-point temperatures (90 °C and 120 °C), measurement of melting time and feed mass per cycle, as well as heat balance calculations separating the contributions of conduction, convection, and radiation on the barrel heated by a band heater. In addition, the power/energy requirement per cycle and productivity projections based on hopper capacity were calculated. The results show that increasing the set-point from 90 °C to 120 °C accelerates melting from ±240 s to ±180 s (≈25% faster). Heat transfer analysis confirmed the dominance of conduction (≈329.7 W at 90 °C and ≈471 W at 120 °C), while convection and radiation contributions were much smaller; the total system heat rate was ≈342.7 W (90 °C) and ≈490.8 W (120 °C). The discussion highlights the process trade-off: higher set-points increase production rate and mold filling quality (due to lower melt viscosity), but may raise energy consumption per cycle and require tighter mold temperature control to limit shrinkage/warpage. The practical implications for SMEs are the need for efficiency strategies based on barrel insulation, heater contact area optimization, and correlation of temperature-time settings with quality and energy consumption targets. This study concludes that controlled temperature and heating duration, supported by simple yet targeted thermal design, can improve cycle time consistency, dimensional precision, and energy efficiency in small-scale plastic bolt molding machines.